Mutations in SARS-CoV-2 ORF8 Altered the Bonding Network With Interferon Regulatory Factor 3 to Evade Host Immune System - Rashid, Farooq; Suleman, Muhammad; Shah, Abdullah; Dzakah, Emmanuel Enoch; Wang, Haiying; Chen, Shuyi; Tang, Shixing (Frontiers in Microbiology, 2021)
SARS-Cov-2 has been continuously mutating since its first emergence in early 2020. These alterations have led this virus to gain significant differences in infectivity, pathogenicity and host immune evasion. We previously found that the open reading frame 8 (ORF8) of SARS-CoV-2 can inhibit interferon production by decreasing the nuclear translocation of interferon regulatory factor 3 (IRF3). Since several mutations in ORF8 have been observed, therefore, in the present study, we adapted structural and biophysical analysis approaches to explore the impact of various mutations of ORF8, such as S24L, L84S, V62L, and W45L, the recently circulating mutant in Pakistan on its ability to bind IRF3 and that may help to evade host immune system. We found that mutations in ORF8 could affect the binding efficiency with IRF3 based on molecular docking analysis, which was further supported by molecular dynamics simulations. Among all the reported mutations, W45L was found to bind most stringently to IRF3. Our analysis revealed that mutations in ORF8 may help the virus evade immune system by changing its binding affinity with IRF3.